Photocatalytic reduction of chromium by titanium metal organic frameworks in the presence of low-molecular-weight organic acids under UV and visible light. Issue 6 (December 2022) - Fatima, Rida; Kim, Jong-Oh
Abstract: The LMWOAs have an α-hydroxy group and dissociate into R-COO .- radicals and electrons. These electrons, along with electrons from the conduction band of photocatalysts, transfer to Cr (VI), reduce it to Cr (III). Here, we explore this phenomenon of under ultraviolet (UV) and visible light, using MIL-125(Ti) and solvothermally modified RG-MIL as photocatalysts, respectively. Tartaric acid (TA) exhibits a greater reduction potential under both UV and visible light. The reduction of chromium increases 1.27-fold and 1.68-fold under UV and visible light, respectively. A maximum reduction efficiency was evident at a pH of 2 and a TA dose of 1 mmol/L for both UV and visible light. Changes in the molecular fingerprints of a photocatalyst after chromium reduction were investigated through Fourier-transform infrared analysis. Negligible changes were observed before and after the reaction, indicating that the structure of the photocatalyst remained largely intact. Mechanism studies show the development of a charge-transfer complex between the photocatalyst and LMWOA. Electrons transfer from the photocatalyst into the chromium, resulting in enhancement of chromium reduction potential. Quantitative investigations of the reduction performance of both systems indicate that MIL-125(Ti) + TA and RGO-MIL + TA are as effective as systems reported previously in the literature. Graphical Abstract: ga1 Highlights: Chromium reduction was studied under both UV and visible light. Titanium based metal organic framework were utilized as photocatalysts. Low molecular weight organic acids were explored to enhance the chromium reduction potential. Addition of tartaric acid resulted in almost complete reduction of chromium in acidic pH. Stability of photocatalyst was studied using Fourier transform infrared spectroscopy.